Molecular Targets of Oxidative Stress: Focus on the Nrf2 Signaling Pathway in Health and Disease - Marcel Bonay (MDPI AG, 2024)
Oxidative stress, known to increase the risk of multiple metabolic and chronic disorders or cancer development, is defined as an imbalance between the production of reactive oxygen species (ROS) and the capacity of antioxidants to counteract the deleterious effects of oxidants [...]